BIOCHEMICAL INDICATORS OF BLOOD SERUM OF RATS OF DIFFERENT AGES AFTER FILLING THE DEFECT IN THE METAPHYSIS OF THE FEMUR WITH ALLOGENEIC BONE IMPLANTS - Vorontsov, Petro; Leontyeva, Frieda; Tuliakov, Vladyslav (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Bone defects that do not heal on their own are a significant problem in orthopaedic and trauma surgery. One of the approaches to its solution is the use of bone alloimplants (AloI). Objective. On the basis of the analysis of biochemical indicators of the metabolism of connective tissue in the blood serum of laboratory rats, the course of metabolic processes after the filling of the defect in the metaphysis of the AloI femur was evaluated. Methods. A model of creating a transcortical defect of critical size (diameter 3 mm, depth 3 mm) in the metaphysis of the femur of 3- and 6-month-old rats was used. In animals of groups I (n = 15, age 3 months) and III (n = 15,12 months) the defects were left unfilled, II (n = 15, 3 months) and IV (n = 15, 12 months) — filled with structural AloI. After 14, 28 and 90 days, the content of glycoproteins, total chondroitin sulphates (CS), protein and calcium, activity of alkaline and acid phosphatases in blood serum was investigated. Results. The introduction of AloI leads to an increase in the content of glycoproteins for all periods of observation in rats of both age groups. 14 days after implantation in 12-month-old rats, compared to 3-month-old rats, a 1.30 times higher level of CS in blood serum was determined (p = 0.008), which is due to their higher content in the area of connective tissue implantation; the activity of alkaline phosphatase decreased by 1.80 times p = 0.016) and acid phosphatase by 1.50 times (p = 0.018), which indicates a delay in the formation and reorganization of bone tissue. However, the level of CS under the conditions of the establishment of AloI on the 90th day was lower compared to the corresponding groups without plasticity of the defect: in 3-month-old rats by 1.44 times ( p = 0.008), in 12-month-old rats by 1.52 times (p = 0.008). Conclusions. According to the indicators of biochemical markers of connective tissue metabolism, the use of AloI for plasticity of defects of a critical size in the metaphysis of the femur of rats leads to the activation of bone regeneration with a greater manifestation in younger recipients compared to groups with an unfilled defect.